Agency and embodiment : performing gestures/producing culture - Noland, Carrie, 1958- (Harvard University Press, 2009)
In Agency and Embodiment, Carrie Noland examines the ways in which culture is both embodied and challenged through the corporeal performance of gestures. Arguing against the constructivist metaphor of bodily inscription dominant since Foucault, Noland maintains that kinesthetic experience, produced by acts of embodied gesturing, places pressure on the conditioning a body receives, encouraging variations in cultural practice that cannot otherwise be explained.